Specificity and sensitivity of a rapid dipstick test (Brugia Rapid) in the detection of Brugia malayi infection - N., Rahmah; S., Taniawati; Shenoy, R.K.; Lim, B.H.; Kumaraswami, V.; Anuar, A.Khairul; Hakim, S.Lokman; M.I., Noor Hayati; Chan, B.T.; M., Suharni; Ramachandran, C.P. (Oxford University Press, 2001)
A total of 753 serum samples from 6 institutions in 3 countries (Malaysia, Indonesia and India) were used to evaluate an immunochromatographic rapid dipstick test, Brugia Rapid, for diagnosis of Brugia malayi infection. The samples comprised sera from 207 microfilaria-positive individuals and 546 individuals from filaria non-endemic areas. The latter consisted of 70 individuals with soil-transmitted helminth infections, 68 with other helminth infections, 238 with protozoan infections, 12 with bacterial and viral infections and 158 healthy individuals. The dipstick is prepared with a goat anti-mouse antibody control line and a B. malayi recombinant-antigen test line. First, the dipstick is dipped into a well containing diluted patient serum, thus allowing specific anti-filarial antibody in the serum to react with the recombinant antigen. Then the dipstick is placed into an adjacent well containing reconstituted anti-human IgG4-gold. After 10 min, development of 2 red-purplish lines denotes a positive result and one line indicates a negative reaction. The overall results of the evaluation showed 97% sensitivity, 99% specificity, 97% positive predictive value and 99% negative predictive value. Brugia Rapid is thus a promising diagnostic tool for detection of B. malayi infection, and would be especially useful for the brugian filariasis elimination programme.